Learning Fun English Using Total Physical Response Method - Zulia Karini (IJECA (International Journal of Education and Curriculum Application), 2018)
One of the difficult parts of learning the target language for English language learners is the acquisition of vocabulary. Most learners find that English is a hard subject to be studied. However, they can enjoy learning English when it is taught in a fun way. Using games for teaching vocabulary has been very popular for several decades. Different studies revealed that games are beneficial in vocabulary learning because they enhance students’ ability to memorize words, encourage student’s interaction, improve their communicative skills and enhance students’ motivation. Games also can help the teachers to create contexts in which the language is useful and meaningful. Watching a movie is also a great way to learn English. Learners can improve their vocabulary while watching a film. Total Physical Response method can also be applied when teaching English for children. This method makes language skills more quickly understood and understood by children the use of functional English like "Show and tell". Fun English learning activities (over English learning) was done this time, considering how enthusiastic the children in Taman Baca Kudi Dusun Cunil Pegalongan village Banyumas in every activity given. This English learning activity also aims to provide English introduction materials early so that they will be accustomed to facing all things related to the English language.